Effect of thyroid dysfunction on N-terminal pro-B-type natriuretic peptide levels: A systematic review and meta-analysis - Zhang, Hongling; Li, Xiaotao; Zhang, Nawen; Tian, Limin (Frontiers in Endocrinology, 2023)
Purpose: Thyroid hormones (THs) significantly affect the cardiovascular system. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a useful biomarker for diagnosing, evaluating, and predicting outcomes in heart failure (HF). This comprehensive review and meta-analysis aimed to investigate the effects of thyroid dysfunction (hypothyroidism and hyperthyroidism) on NT-proBNP levels. Methods: Two investigators independently searched PubMed, Embase, Cochrane Library, and Web of Science databases for studies published from inception to July 31, 2022, without any restrictions on language. Results: 21 studies were included. In participants without HF, NT-proBNP levels may be elevated in those with overt hyperthyroidism (standardized mean difference [SMD] 2.38, 95% confidence interval [CI]:1.0-3.76). Notably, among patients with preexisting HF, significantly higher NT-proBNP levels were found in patients with overt hyperthyroidism, overt hypothyroidism, or subclinical hypothyroidism than in euthyroid subjects (SMD [95%CI] = 0.31[0.01, 0.62], 0.32[0.08, 0.56], and 0.33[0.21, 0.46], respectively). Seven trials compared NT-proBNP levels in patients with thyroid dysfunction before and after therapy, and significant drops in NT-proBNP levels were observed in patients with hyperthyroidism (SMD [95%CI] = -1.53[-2.50, -0.55]) upon achieving a euthyroid state. In contrast, increased NT-proBNP levels were observed in hypothyroid patients after treatment (SMD [95%CI] = 1.07[0.28, 1.85]). Conclusion: Thyroid dysfunction can significantly affect NT-proBNP levels, which may change upon achieving a euthyroid state. Notably, the effect of thyroid dysfunction on cardiac function may depend on the underlying cardiac status. Thus, timely recognition and effective treatment of cardiac symptoms in patients with thyroid dysfunction are mandatory because the prognosis of HF may be improved with appropriate treatment of thyroid dysfunction.